Fabrication of polymer/drug‐loaded hydroxyapatite particle composite fibers for drug sustained release. Issue 3 (8th September 2015) - Song, Botao; Xu, Qing; Wang, Cuiyu; Xu, Shichen; Zhang, Hongxin
ABSTRACT The aim of this study is to fabricate polymer/hydroxyapatite (HA) particle composite fibers for drug encapsulation and sustained release. Firstly, drug‐loaded hydroxyapatite particles are synthesized in one step, then by electrospinning of the blends of drug‐loaded hydroxyapatite particles and polymer solution the drug‐loaded polymer/hydroxyapatite particle composite fibers are successfully prepared. Effect of loading ratio of drug‐loaded hydroxyapatite particles in the fibers and pH value of the release medium on the drug release kinetics are both investigated, and the results demonstrate that, as compared with the polymer/drug electrospun fibers, the drug in the polymer/drug‐loaded hydroxyapatite particle composite fibers shows a sustained release manner, and the drug release rate can be regulated by both the loading ratio of drug‐loaded hydroxyapatite particles in the composite fibers and pH value of the buffer solution. The results indicate that the developed drug‐loaded polymer/hydroxyapatite particle composite fibers show great potential in bone regeneration and other related biomedical fields. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42871.